THE EFFECTIVENESS OF THE PROBLEM-BASED LEARNING MODEL ON FLAT-SIDED GEOMETRICS MATERIAL ON STUDENTS CRITICAL THINKING ABILITIES AT SMPN 1 KAJEN - Zahra, Lailatuz; Nalim, Nalim (STAI Al-Bahjah, 2024)
Mathematics aims to improve skills such as reasoning, critical thinking and problem solving in order to prepare students for life and further education. However, mathematics is generally considered a science that does not allow for critical thinking. In the learning process, most students are passive in solving mathematical problems so they cannot practice their critical thinking abilities The main aim of this research is to find out whether the problem-based learning model is effective on students' critical thinking abilities. This study uses a quantitative approach. This research is used a type of quasi-experimental research (quasi-experimental). The population of this study was all class VIII students at SMPN 1 Kajen, totaling 288 students. The sample from this research was 64 students consisting of an experimental class that applied a problem-based learning model and a control class that applied conventional learning. The results of this research show that the critical thinking abilities of students who receive the problem-based learning model are significantly different from students who receive the conventional learning model. The N-Gain test results show the effectiveness of the learning process. The use of problem-based learning models produces better critical thinking abilities compared to conventional learning models.